Building Information Modeling Strategy in Mitigating Variation Orders in Roads Projects - Musab Abuaddous; Ja’far A. Aldiabat Al-Btoosh; Mohammed A. KA. Al-Btoush; Abdulrazzaq Jawish Alkherret (Salehan Institute of Higher Education, 2020)
Most governmental projects in Jordan have cost overrun, it rises during the on-going stage to increase the cost and prolong the time of the project. Unfortunately, until this moment, there is no particular management system in Jordan construction industry to minimize cost overrun and variation order adopted by the government. In contrast, global construction industry has witnessed a huge transformation in terms of the use of digital technologies, particularly Building Information Modeling (BIM) which is a revolutionary digital technology and operation that is reshaping the Architecture, Engineering and Construction (AEC) industry. approach and objectives causes before of this paper are firstly to review the factors contributing to variation orders in governmental road projects in Jordan, secondly, to propose a BIM design applications strategy to minimize variation orders, to achieve the objectives a quantitative approach was followed by distributing a questionnaire, then the data was analyzed statistically using relative importance index, the results were as follow. Our findings suggests that the most important factors causing change orders were as follow: Inaccurate quantity take-off (0.66); Labours or material not meeting the specifications (0.63); Logistic delays (0.60); Internal politics (0.566); and the equipment and tools are not available (0.55). The results also indicate that Contract Parties, Consultant, Contractor and Other Variations had significant positive effects on V. O, whereas the effects of BIM Design Applications, Facility Operations Simulation, Exploration Design Scenarios, BIM Design Detection, (BIM Quantity Take-off and Cost Estimation) had a passive impact on V.O. Lastly, BIM has obtained a great reputability by enhancing the productivity in construction society, minimizing the total cost of the projects, and many other benefits.